Local Strength-Based Human Resource Management Strategy for Developing the Quality of MTsN 3 Malang - Diyah Suryaningsih (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2021)
The enactment of Government Regulation Number 19 of 2005 concerning National Education Standards, followed by several Permendiknas as its elaboration, is a major challenge for improving the quality of madrasas which are managed through management based on local strengths. The purpose of this study is to describe the human resource management policies at MTsN 3 Malang, the management achievements, local strengths that characterize their development, as well as an analysis of challenges and effective steps in implementing human resource management policies. Based on the description of descriptive data using qualitative research methods carried out at MTsN 3 Malang, it is known that human resource management policies at MTsN 3 Malang are carried out based on a combination of government regulations and madrasah policies. Based on the current condition of human resources, the placement of teaching and educational staff is not in accordance with the needs, both in number and qualifications. The effectiveness of implementing local strength-based management at MTsN 3 Malang is related to the principles of madrasah leadership, basic skills and abilities of teachers and employees, commitment in implementing management to understand each other, respect each other, be mutually responsible for a job at hand, with the motto of sincere charity. Challenges in the implementation of human resource management policies that occurred at MTsN 3 Malang, both internal challenges and external challenges, can be overcome by carrying out teacher and employee quality development programs through quality improvement programs, developing and optimizing the use of infrastructure facilities, awarding policies for teachers and outstanding employees to spur the creativity of teachers and employees in their daily performance.